148k views
0 votes
The 3rd term of an arithinetic progression is-9

and the 7th term is -29. Find the 10th term of the
progression.​

1 Answer

3 votes

Answer:

-64

Explanation:

The computation of the 10th term of the progression is shown below:

The 3rd term is -9

A_n = a + (n - 1)d

-9 = a + (3 - 1)d

-9 = a + 2d

-9 - 2d = a

Now the 7th term is -29

A_n = a + (n - 1)d

-29 = a + (7 - 1)d

-29 = a + 6d

Put the a value to the above equation

-29 = -9 - 2d + 6d

-29 + 9 = 4d

-20 = 4d

d = -5

Now

-9 - 2d = a

-9 - 2(-5) = a

-9 - 10 = a

a = -19

Now finally the 10th term of the progression is

= a + (n - 1)d

= -19 + (10- 1)-5

= -19 -45

= -64

User Ningk
by
6.1k points